2004
DOI: 10.1007/s00381-004-1008-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of a compact intraoperative low-field magnetic imager in pediatric neurosurgery

Abstract: The low-field PoleStar -10 iMRI system can safely assist pediatric neurosurgeons treating a variety of diseases. In addition to neuronavigation it provides information on extent of resection, real-time guided catheter placement, and avoidance of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…We achieved a resection rate of 82% in a smaller cohort of 22 pediatric patients using IOUS. Samdani et al demonstrated that a low-field iMRI in pediatric neurosurgery provides additional information for resection and real-time catheter placement [22], which we could also confirm with the IOUS technique. To date, there are no published prospective randomized studies comparing outcomes and resection control percentages between these two intraoperative imaging modalities.…”
Section: Intraoperative Imaging and Ioussupporting
confidence: 72%
“…We achieved a resection rate of 82% in a smaller cohort of 22 pediatric patients using IOUS. Samdani et al demonstrated that a low-field iMRI in pediatric neurosurgery provides additional information for resection and real-time catheter placement [22], which we could also confirm with the IOUS technique. To date, there are no published prospective randomized studies comparing outcomes and resection control percentages between these two intraoperative imaging modalities.…”
Section: Intraoperative Imaging and Ioussupporting
confidence: 72%
“…[3][4][5][6][7][8][9][10][11] However, the benefits of this expensive technology have not been uniformly demonstrated in the literature. [11][12][13][14] With respect to high-field-strength iMRI, typically defined as 1.5T or higher, its impact on operating room and anesthesia time and the incidence of MR imaging-related complications, particularly in the pediatric population, have been the topic of limited publications. 3,[15][16][17] We performed a retrospective review of our 24-month experience with a 3T-iMRI at a tertiary care children's hospital to determine the impact of this tool on surgical planning, workflow, and patient outcomes.…”
mentioning
confidence: 99%
“…iMRI may also have applications specific to pediatric neurosurgical issues [7]. This paper reviews our experience using the 0.12-tesla iMRI system for various neurosurgical procedures in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%